Predicting the scale of tennis rackets for optimal striking from body dimensions - Gagen, L.; Haywood, H.; Spaner, S. D. (Pediatric Exercise Science, 2005)
This study tested the hypothesis that scaling environmental objects can afford differently sized individuals the opportunity to make similarly effective movements with that object. Four similar tennis rackets were scaled to provide consistent differences in length, weight, and grip size. Children between 4 and 10 years of age were asked to strike with each racket for speed and accuracy. A significant relationship existed between body size and strength and the ability to both generate racket head speed and control the racket for an accurate strike; racket size and weight, however, were not significant factors in the ability to swing effectively.